Quality of minimally processed guava with different types of cut, sanification and packing - Marilene Silva LIMA (Ciência e Tecnologia de Alimentos, 2010)
The purpose of this project was to evaluate the sanitization effect on the quality of minimally processed guava. Initially, research was carried out with consumers in a supermarket to verify preferences of packaging for guava. Following this, the guava cv. Paluma underwent two sanitization sequences using dehydrated sodium dichloroisocyanurate compound, in 50 ppm concentration, sanitization prior to (S1) and after (S2) being cut; removal of excess water; conditioning in PET packaging and PS-PVC and storage at 3 °C ± 1 °C. Physicochemical analysis – [pH, total soluble solids (SST), total labeled acidity (ATT), ascorbic acid (AA), total sugars (AT) and reducers (AR)], textural sensorial and microbiological analyses were used to monitor the quality of the products. The consumers preferred the guava cut in halves with pulp and packed in PET, although this packaging promoted condensation of water vapor on the inner surface of the lid, compromising the appearance of the product. The two sanitization sequences and the two kinds of packaging did not significantly affect the pH, SST, ATT, SST/ATT, texture and AA values. The AT and AR tenors increased significantly in the MP guavas stored in the PS-PVC package. Both sanitizations were efficient in the bacterial control of the indicators of the hygienic-sanitary conditions, although the S1 sanitization proved to be more efficient in the control of autochthonous aerobic microbiota (aerobic mesophylic microorganisms). It can be concluded that guava cv. Paluma packed in PS-PVC can be conserved for 6 days when stored at 3 °C.